(untitled) (Jurnal Ekonomi dan Kebijakan Pembangunan, 2025)
The main focus of this research investigates the role of investment, which in this study is divided into: foreign direct investment and domestic investment, and the extent of their respective contributions in achieving inclusive growth in Indonesia. This study uses fixed effect methodology with panel data analysis of 34 provinces in Indonesia. In general, the evolution of investment in Indonesia is still dominated by certain regions, centred in Java Island. Furthermore, regarding inclusive growth, we use 3 measurement indicators that have been adjusted by Bappenas. Our findings from this research are that foreign direct investment has not been able to optimally become a driving force for inclusive growth. Foreign direct investment will be efficiently impactful when technology is used as an accelerator to achieve high economic growth. Apart from that, this study also reveals that domestic investment has not had a significant impact on inclusive growth but has significantly influenced the distribution of people’s income. Additionally, we found that education is the only thing capable of contributing to inclusive growth. Education has an impact on high economic growth, can increase income equality or reduce poverty, and at the same time increase the expansion of access and opportunities.